Systematic impacts of early-adolescent experiences on behavioral development: Insights from the “Human‐Rat Interaction Paradigm” - Wu, Xiaorui; Yin, Bin; Yu, Delin; Li, Hong (Cognitive development, 2025)
Utilizing human experimenters as surrogate caretakers and one-month-old male Sprague-Dawley rats as child proxies, this study introduces the “Human-Rat Interaction Paradigm” (HRIP) to explore the systematic impact of early-adolescent experiences on behavioral development. Over a three-week intervention, rats were assigned to positive early-adolescent experiences (PEE), negative early-adolescent experiences (NEE), or a control group. By the second week, behavior stabilized. A series of assessments reveal that PEE rats showed lower anxiety and adapted quickly to new environments. In contrast, NEE rats exhibited early procedural learning but inadequate long-term memory retention. PEE rats were more interested in toy rats, while NEE rats displayed aversion; both groups preferred unfamiliar rats. In empathetic scenarios, both groups hesitated to share food with a trapped peer; NEE rats, in particular, showed increased vigilance and feeding interruptions. Social competition tests revealed distinct strengths and weaknesses, with the PEE group maintaining a more stable social hierarchy. Control rats, though less responsive to socio-environmental variations, consistently performed well in status-based (non-food reward) competitive settings. These findings highlight the significant role of early-adolescent experiences in shaping emotional, cognitive, and social behaviors, underscoring the translational value of HRIP as a developmental research model. •The “Human-Rat Interaction Paradigm” models systematic early-adolescent caregiving.•Positive experiences reduce anxiety, enhancing exploration and adaptability.•Negative experiences heighten vigilance, disturbing emotional and goal-directed behaviors.•Absence of enriched experiences dulls responses in complex learning and social tasks.•Early interactions with people and objects shape security and connection dimensions.